Masking agent-free and channel-switch-mode simultaneous sensing of Fe3+ and Hg2+ using dual-excitation graphene quantum dots1. Issue 12 (21st June 2015) - Xu, Fengzhou; Shi, Hui; He, Xiaoxiao; Wang, Kemin; He, Dinggeng; Yan, Lv'an; Ye, Xiaosheng; Tang, Jinlu; Shangguan, Jingfang; Luo, Lan
<x xml:space="preserve">Abstract</x> Utilizing dual-excitation single-emission graphene quantum dots, a novel channel-switch-mode strategy for simultaneous sensing of Fe3+ and Hg2+ is developed.